Comunicação, consumo de conteúdos violentos e questões éticas na comunidade virtual ''Ilha da macacada'' - Mazurek, Mike Akama (2018)
Based on the relationship between the fields of communication and consumption, we seek to think about ethical issues in the Facebook group "Ilha da Macacada", which has a total of eight hundred thousand members and dedicated almost exclusively to violent content or actions. Specifically, this dissertation tries to problematize the censorship of the consumption and the reproduction of violent contents in the analyzed group. To develop this research, a virtual ethnography is carried out within the "Island of the Macacada", from which to understand the dynamics of the consumption of violent content and to problematize the ethical issues that permeate the consumption of these contents in SRS like Facebook.